Creating a framework for talent identification and development in emerging football nations - Bennett, K. J. M.; Vaeyens, R.; Fransen, J. (Science and Medicine in Football, 2019)
Talent identification and development in football is a complex, multifaceted process. Currently, most of the research in this domain is conducted in highly ranked, established football nations where the sport is immensely popular (e.g. Germany, Portugal, Belgium, etc.). Whilst these nation`s data are informative to some degree, there is little conclusive evidence supporting the effectiveness of traditional talent identification approaches. Typically, talent identification involves actively selecting promising players with early performance superiorities without considering the changes that can occur during development. Consequently, it is difficult to develop a framework for emerging football nations as the repercussions of adopting traditional approaches to talent identification are likely greater due to differences the size of the talent pool, accessibility of systematic training environments, and availability of financial and logistical resources. It is proposed that emerging football nations should focus on: preventing active deselection and dropout to maximise the size of the talent pool, mitigating the influence of confounding factors on talent identification, and longitudinally tracking players throughout development to document the performance profiles that lead to football expertise. Collectively, these strategies can reduce the reliance on identifying players based on early performance superiorities and focus on holistic, long-term development.